The Aesthetic-Historical Experience. Regarding Frank Ankersmit’s Concept - Piętka, Aleksandra (Załącznik Kulturoznawczy, 2024)
This paper discusses Frank Ankersmit’s concept of historical experience and the pivotal role of historical subject’s individual perception in experiencing the past. The author delves into Ankermit’s analysis of Francesco Guardi’s 18thcentury capriccio Arcade with a Lantern, an artwork whose structure, according to the historian, is identical with defining features of what he calls a subjective historical experience. Following the analogy of subjective historical experience and aesthetic experience and Jonathan Clark’s ontological implications of Ankersmit’s theory, the author explores the relationship between the subject and object of the experience. Finally, using the example of contemporary architectural work, it is demonstrated how interaction with an artwork enables us access to the past, even though its creator did not live in the times he refers to.